PENGARUH DARK TRIAD TERHADAP HUBUNGAN ANTARA ENTREPRENEURIAL ATTITUDE ORIENTATION DAN ENTREPRENEURIAL INTENTION PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Fikri Faidul Jihad, Nurlina (Departemen Manajemen, 2019)
This study aims to examine the influence of Dark Triad on the relationship between Entrepreneurial Attitude Orientation and Entrepreneurial Intention on undergraduate student S1 Faculty of Economics and Business of Syiah Kuala University. Sampling method in this study using stratified random sampling with a sample of 240 respondents in each department of the Faculty of Economics and Business. The results showed that Entrepreneurial Attitude Orientation influence to Entrepreneurial Intention positively and significantly. Dark Triad has a significant negative relationship both on Entrepreneurial Attitude Orientation and Entrepreneurial Intention. Mediation testing showed Dark Triad variables mediate partially on Entrepreneurial Attitude Orientation and Entrepreneurial Intention.Keywords: Entrepreneurial Attitude Orientation, Entrepreneurial Intention, Dark Triad